Genetical and statistical aspects of polymerase chain reactions - Marcus Brunnert; Oliver Müller; Wolfgang Urfer (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2000)
In this paper we describe the principles of polymerase chain reaction (PCR) and its expanding use in molecular genetic research and molecular medicine. A short introduction of exemplary applications of the PCR is connected with a discussion of the lack of PCR accuracy. We give a statistical model for the PCR and discuss estimation methods in order to quantify the lack of PCR accuracy.
Keywords: 519; Polymerase chain reaction; lack of PCR accuracy; branching process; estimation of the mutation rate